Small RNA data sets of mouse testes and ovaries before and after sexual maturity - Mailin Gan; Xingyu Wang; Jianfeng Ma; Lei Chen; Yan Wang; Linyuan Shen; Li Zhu (Scientific Data)
Abstract For a considerable period, reproductive health, fertility, and reproductive-related diseases have posed challenges to human well-being, as well as to the conservation of endangered species and the advancement of animal husbandry. PANDORA-seq, a recently introduced sequencing technique, demonstrates heightened sensitivity towards highly modified small RNAs like tsRNA and rsRNA. In this research endeavor, we leveraged PANDORA-seq to capture the small RNA expression profiles of mouse testes and ovaries pre- and post-sexual maturation. Our investigation successfully pinpointed an array of abundantly expressed small RNAs across various tissues, encompassing tsRNA, rsRNA, piRNA, miRNA, snoRNA, and ysRNA. Next, we conducted an expression profile analysis of these small RNAs to assist researchers in screening and validating them for various areas of interest. This dataset is poised to become an invaluable resource for exploring the postnatal development of testes and ovaries, offering new insights into the epigenetic mechanisms underlying germ cell production and differentiation.